International relations a beginner's guide - Jones, Charles A. 1949- (Oneworld, 2014)
Cover; Title Page; Copyright; Dedication; Contents; Abbreviations; List of Figures; Preface; 1: What is international relations?; The Leading Actors: States and Intergovernmental Organizations; International Non-governmental Organizations; Globalization and the Widening IR Agenda; Migration; What's in a Name? - International Politics, Relations, Affairs, and Studies; International Politics v. International Relations; 2: The shadow of history; An Outline of World History; Empire and Industry; Histories: Universal, Conjectural, Modern, and Contemporary; Cultivated Forgetfulness
Keywords: Internationale Politik; International relations